Public-private partnership in health care - a tool for the development of public medical insitutions - Chopchik, V. D. (Journal of Education, Health and Sport, 2019)
Introduction. International experience accumulated over the past 25-30 years suggests that PPP is one of the main mechanisms for expanding the resource base and mobilizing reserves for economic development and improve the effectiveness of public health care. Objective: To substantiate the possibility of public-private partnership (PPP) use in healthcare as a strategic goal, a tool for its development. Materials and methods. To achieve the objective mentioned general scientific methods of analysis, synthesis, substantiation, interpretation of scientific data, as well as systemic and structural-functional approaches were used in the work presented. The information base of the study was the academic works of domestic and foreign experts in PPP and management. Results. The development of health care on the principles of PPP as the main tool for achieving sustainable development of Ukrainian health care in the long term has been analyzed. Recent years Ukrainian budget is scarce and this causes a lack of financial resources that could be used to increase the efficiency of medical services provision. The limited financial resources received by state and communal medical institutions are the reasons of their poor material and technical equipment, lack of modern technologies, decent remuneration of medical and scientific personnel. All this makes it necessary to introduce new, more effective forms of organizing the activities of state and communal healthcare institutions, including PPP principles. The article substantiates the mechanisms of PPP as a tool for the development of health care. Conclusions. Based on Ukrainian economic situation the justification of a more effective form of organizing the activities of state and communal healthcare institutions based on PPP principles, reasonably forms the strategic goals of healthcare development in this country and determines the directions for the implementation of healthcare functions in accordance with the environmental conditions.